Intelligent Tenaga Nasional Berhad (TNB) Single Phase Power Supply Cut-Off - Ab Aziz, Ab Wafi; Rahim, Norain; Amirhussain, Amir Hariz; Norddin, Nur Bahirah (Penerbit Universiti, UTeM, 2017)
This paper presents the development of an Intelligent Tenaga Nasional Berhad (TNB) Single Phase Power Supply Cut-off by using Internet of Things (IoT) technology. This project offers a new method for TNB to replace their traditional approaches; pulling-out the fuselink near the electrical meter to cut the electricity supply. The available system may cause difficulties to TNB because their workers need to go to the meter location, which located inside the gated or inaccessible area. This situation requires TNB to send their workers back until the problem is resolved. Through this intelligent system, TNB workers no longer has constrains to go to the customers’ premises to plug-in or plug-out the fuselink and the electricity supply can be switched on or off via WiFi connectivity. A web server is used as a user interface to control the programmable NodeMCU that is attached to the main supply. To cut-off or turn-on the power supply, an authorized worker can access this interface through smart phone. To control the power supply, a worker needs to connect their smart phone to the NodeMCU using the WiFi connection and then selects the ‘OFF/ON’ button on the web server interface. Once the ‘OFF’ button is selected, relay that is connected to the main power supply will trigger to cut-off the main power supply. All these can be accomplished without the need for the worker to be presence nearby the electrical meter. The WiFi coverage for this project is up to 150 meters, which is far enough to communicate with the meter located inside a gated area. The response of the relay increases with increase of the distance. However, it can still be considered as fast response since it is only up to 150 miliseconds.